Long-Term Saccharin Consumption and Increased Risk of Obesity, Diabetes, Hepatic Dysfunction, and Renal Impairment in Rats - Omar Hasan Azeez; Suad Yousif Alkass; Daniele Suzete Persike (Medicina, 2019)
Background and objectives: This study evaluated the effect of chronic consumption of saccharin on important physiological and biochemical parameters in rats. Materials and Methods: Male Wistar rats were used in this study and were divided into four groups: A control group and three experimental groups (groups 1, 2, and 3) were treated with different doses of saccharin at 2.5, 5, and 10 mg/kg, respectively. Each experimental group received sodium saccharin once per day for 120 days while the control group was treated with distilled water only. In addition to the evaluation of body weight, blood samples [total protein, albumin, glucose, lipid profile, alanine transaminase (ALT), aspartate transaminase (AST), lactate dehydrogenase (LDH), creatinine, and uric acid] and urine (isoprostane) were collected in zero time, and after 60 and 120 days for biochemical evaluation. Liver (catalase activity) and brain (8-hydroxy-2’-deoxyguanosine, 8-OHdG) tissues were collected at time zero and after 120 days. Results: The data showed that saccharin at 5 mg/kg increased body weight of treated rats after 60 (59%) and 120 (67%) days of treatment. Increased concentration of serum glucose was observed after treatment with saccharin at 5 (75% and 62%) and 10 mg/kg (43% and 40%) following 60 and 120 days, respectively. The concentration of albumin decreased after treatment with saccharin at 2.5 (34% and 36%), 5 (39% and 34%), and 10 mg/kg (15% and 21%) after 60 and 120 days of treatment, respectively. The activity of LDH and uric acid increased proportionally with dosage levels and consumption period. There was an increased concentration of creatinine after treatment with saccharin at 2.5 (125% and 68%), 5 (114% and 45%), and 10 mg/kg (26% and 31%) following 60 and 120 days, respectively. Catalase activity and 8-OHdG increased by 51% and 49%, respectively, following 120 days of treatment with saccharin at 2.5 mg/kg. Elevation in the concentration of isoprostane was observed after treatment with saccharin at all doses. Conclusions: The administration of saccharin throughout the treatment period was correlated with impaired kidney and liver function. Both hyperglycemic and obesity-inducing side effects were observed. There was an increased oxidative status of the liver, as well as exposure to increased oxidative stress demonstrated through the increased levels of isoprostane, uric acid, 8-OHdG, and activity of catalase. Therefore, it is suggested that saccharin is unsafe to be included in the diet.